2010
DOI: 10.1583/09-2920.1
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Methodology for Investigating the Parameters Influencing Migration Resistance of Abdominal Aortic Stent-Grafts

Abstract: Assessing the migration resistance of stent-grafts based solely on proximal fixation discriminates against devices that are longitudinally stiff. Current in vivo models may give inaccurate displacement forces due to the high degree of oversizing in these studies. A novel in vitro approach, accounting for longitudinal rigidity and realistic graft oversizing, was developed to determine the resistance of aortic stent-grafts to migration in the period immediately after device implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…So far, only a handful of studies have tried to assess the fixation of various EVAR devices, mainly in DF tolerance in human cadaveric, 11,14,16,17 in vivo ovine, 1,2 and cadaveric ovine 20 aortas, or in silicone models. 21 This is the first analysis to include the Aorfix and Aptus devices.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only a handful of studies have tried to assess the fixation of various EVAR devices, mainly in DF tolerance in human cadaveric, 11,14,16,17 in vivo ovine, 1,2 and cadaveric ovine 20 aortas, or in silicone models. 21 This is the first analysis to include the Aorfix and Aptus devices.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in Corbett et al [ 14 ] and shown in Additional file 1 : Table S4, silicone rubbers are good for AAA physical modelling due to high transparency and flexibility but struggle with barbed and hooked stent graft placement simulation due to low tear resistance.…”
Section: Methodsmentioning
confidence: 99%
“…Physical models of aneurysms (both abdominal aortic and cerebral) have been manufactured for a variety of scientific purposes; inclusion in experimental flow systems to study flow patterns and pressures [ 11 , 12 ] for validation of rupture site prediction made using finite element analysis [ 13 ], for laboratory investigations of migration of stent grafts [ 14 ], and in experimental systems for simulation of interventional procedures [ 9 , 10 , 15 ]. Manufacturing techniques may be broadly divided between casting techniques and 3D printing.…”
Section: Introductionmentioning
confidence: 99%
“…The representative 3D AAA model has been widely used in previous publications (Doyle et al 2009;Corbett et al 2010Corbett et al , 2011 and is based on average sizes taken from the Eurostar Data Registry System 2001, as shown in Figure 1(A) with a bifurcation angle u of 608. The photoelastic model has been previously described by Morris et al (2004).…”
Section: Photoelastic Model Creationmentioning
confidence: 99%